School-Based Screening for Suspected Epileptic Seizures Using the UWIMONA Questionnaire Among Elementary School Children in Tulikup Village, Bali, Indonesia: A Cross-Sectional Study - I Gusti Ngurah Agung Jayadhi Widyakusuma; I Gusti Ngurah Made Suwarba; Dewi Sutriani Mahalini (Journal of Educational Studies, 2026)
Epilepsy is a major neurological illness worldwide, and early case detection is essential for treatment. School-based screening may help detect epileptic children in resource-constrained locations. The aim of this study was to evaluate the outcomes of a school-based screening program for suspected epileptic seizures using the UWIMONA Pediatric Epileptic Seizure Screening Questionnaire at an elementary school in Tulikup Village, Bali, Indonesia. We conducted a cross-sectional screening among grades I–VI students at a public elementary school. The UWIMONA questionnaire includes 10 yes/no questions; the total score equals the number of 'Yes' responses (0–10). Screen-positive was defined as a score ?1. We report descriptive statistics and 95% Wilson confidence intervals (CI). A total of 158 students were screened. In the primary analysis using question-level recalculation, 29 students screened positive (18.4%; 95% CI 13.1–25.1). The most frequently endorsed questions were question 1 (10.1%), question 7 (7.6%), and question 10 (6.3%). One student (0.6%) had a maximum score of 10. Nearly one in five students screened positive using a low threshold (score ?1), highlighting the feasibility of school-based screening but also the need for confirmatory clinical evaluation to differentiate true epilepsy from false positives. Future work should include diagnostic verification, evaluation of screening accuracy in the local context, and linkage to care pathways.